Non-microbial natural products that inhibit drug-resistant Staphylococcus aureus - Chew, Jactty *; Peh, Suat Cheng *; Teow, Sin Yeang * (InTech Open, 2018)
Drug resistance developed in human pathogenic bacteria is emerging and has become a global problem. Methicillin-resistant Staphylococcus aureus (MRSA) spreading in both hospital and community areas has posed a great impact to global public health. Current antibiotics used against these resistant strains are no longer efficacious and the search for new alternative is in urgent need. In the past decades, natural products have demonstrated multiple biological activities in biomedical areas including their antibacterial actions against various drug-resistant bacteria. More promisingly, some natural products could reverse the resistance of bacteria to the antibiotics, making the target bacteria susceptible to these drugs again. Numerous natural products have also exhibited potent synergism against the drug-resistant bacteria when used in combination with various types of antibiotics. Recently, several antibacterials derived from microbes have been developed and approved by Food and Drug Administration (FDA) for clinical use. In this chapter, we discuss the potential use of non-microbial natural products in controlling Staphylococcus aureus (S. aureus)‘s growth, and the underlying challenges in developing the natural products into clinical applications.